A Case Report of Conventional Solid Ameloblastoma presenting with Non-Classical Features - K S Ganapathy; S Latha; Anuj Paul Maini (Wolters Kluwer Medknow Publications, 2005)
Ameloblastomas constitute approximately 1 percent of all cysts and tumors of the jaws. The occurrence in the mandible is four times higher than in the maxilla; in the mandible there is a predilection for the molar-ramus area with a little more than two-thirds occurring in this region. The tumor is relatively uncommon anteriorly. The average age of occurrences is in the third or fourth decade. They can grow quite large without metastasizing. The selection of treatment for an individual ameloblastoma depends to a large extent on its clinical type i. e. whether the tumor is a typical intraosseous solid or Multicystic ameloblastoma with poorly defined margins. Other factors of importance are its location in the jaws and its size, the age of the patient and patients availability for follow up examination.